Analisis Usability Aplikasi LegoBoost Builder Dengan Metode System Usability Scale - Henanda, Yestrada; Wahyu Hidayat, Eka; Putra Aldya, Aldy (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
The objective of this research is to evaluate and analyze the usability of the LegoBoost Builder application by employing the System Usability Scale (SUS) method. The LegoBoost Builder application is an in-house developed product by Lego Corporation, featuring animations of robot models that can be assembled using Lego kits. The application is intended for user as an interactive learning tool for animation and robotics. The selection of the System Usability Scale (SUS) method is considered an appropriate and significant evaluation approach to measure the usability of the application. Based on the conducted tests, the LegoBoost Builder application obtained an average of 70.52, categorizing it as GOOD with grade scale C. This score indicates that users find the application useful and beneficial in the educational context. In other words, the LegoBoost Builder application has fulfilled the needs and goals of users in supporting the learning process of animation and robotics.